EFFECT OF USING SOPHIA WITH DIFFERENT ALCOHOL CONCENTRATION ON PH, MOISTURE CONTENT AND ORGANOLEPTIC QUALITY OF NA'AN MARAN (DRIED MEAT) - Ximenes, Carmelita De Araujo; Malelak, Gemini Ermiani Mercurina; Manu, Arnold Elyazar (Jurnal Sain Peternakan Indonesia, 2025)
The purpose of this study was to determine the effect of Sophia concentration with different alcohol concentrations in the processing of Na'an Maran (dried meat), which was conducted at the Animal Product Technology Laboratory, Faculty of Animal Husbandry, Marine and Fisheries. Using 20 kg of fresh beef, Sophia with 10%, 12% and 14% alcohol concentration and 2% salt per 1 kg of meat. This study employed four treatments and five replicates. Where P0: Beef + 2% salt (Control), P1: Beef + 2% salt + 10% alcohol concentration, P2: beef + 2% salt + 12% alcohol concentration, P3: beef + 2% salt + 14% alcohol concentration.  Furthermore, organoleptic properties, pH and moisture content were tested. The data obtained were analysed using ANOVA and followed by Duncan's test to determine if there were significant differences between treatments. Organoleptic data were analysed using the Kruskal-Wallis non-parametric test, followed by the Mann-Whitney test if significant differences were found.  The results showed that the use of Sophia with different alcohol concentrations had a significant effect (P < 0.01) on organoleptic properties and pH, while having no significant effect (P > 0.05) on water content. It can be concluded that Sophia can improve the organoleptic quality of Na'an Maran with the best treatment at 10% alcohol concentration.